Sistem Kontrol dan Monitoring Kualitas Air pada Kolam Ikan Air Tawar menggunakan Logika Fuzzy berbasis Arduino - Yosia Nindra Kristiantya; Eko Setiawan; Barlian Henryranu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Control on the water quality of freshwater fish ponds is the main thing that must be considered, whether consuming freshwater fish or ornamental freshwater fish. Fish pond water quality parameters that can be controlled for example are temperature and ammonia as parameters that can affect the survival and lifestyle of fish. To overcome this, a water quality control and monitoring system is needed in freshwater fish ponds that can help with these problems. This system receives the results of sensor readings which will later be processed in the microcontroller using the fuzzy method to determine the output of the system. The temperature sensor used is the ds18b20 sensor. Based on the tests that have been carried out in this study, the average value of the reading error from the ds18b20 sensor is 0.95%. The ammonia sensor used is the mq-135 sensor, based on the tests that have been carried out in this study, the average error value of the mq-135 sensor reading is 0%. The Sugeno model fuzzy method used in this study after testing the value with an average error of 3.92%. The system is able to run computations from fuzzy method calculations with an average time of 1.4 seconds